DASAR WAJIB PATUH PADA UNDANG-UNDANG PERKAWINAN (UUP) DALAM KONTEKS INDONESIA - Mustakim, Ahmad; Shinwanuddin, M. (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2024)
This article aims to address the ambiguity or phenomenon developing in society regarding the obligation to comply with the Marriage Law in Indonesia. This is because Indonesians possess dual identities: as Muslims who must follow the rules of our religion, and as citizens of Indonesia who are required to adhere to the laws in force in Indonesia (Positive Law). These dual identities among Indonesian Muslims can become a serious issue if we are not wise in making decisions, especially regarding marriage. As Indonesian citizens and Muslims, we are obliged to comply with the Marriage Law because, as citizens of Indonesia, we are certainly required to follow it. This article addresses this issue by stating that the obligation to comply with the Marriage Law, when aligned with the Qur'an, can be found in Surah al-Nisa' (4:59) as a legal argument. This position arises because, in addition to being commanded to obey Allah and the Prophet, we are also commanded to obey those in authority (Ulil Amri), who, in the context of Indonesia, refers to the government/leaders. The relevance of the Marriage Law to Ulil Amri is that the Marriage Law is a product of the government. Ulil Amri includes a combination of leaders, Umara, and society working together for the welfare of the community, which means that as Indonesians and Muslims, we are obliged to obey it.